2008
DOI: 10.1293/tox.21.73
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Mitochondria in the Hepatocytes Induced by Administration of a Large Amount of Di (2-ethylhexyl) phthalate (DEHP) to Cynomolgus Monkeys (Macaca fascicularis)

Abstract: Abstract:The purpose of this study was to determine the relation between administration of a large amount of Di (2-ethylhexyl) phthalate (DEHP) and peroxisome proliferation in cynomolgus monkey (Macaca fascicularis) hepatocytes. DEHP was administered orally to four cynomolgus monkeys, once daily for 28 days at dose levels of 1,000 and 2,500 mg/kg/day. Enlargement of the mitochondria, and lamellar orientation of the cristae along the major axis of the mitochondria were observed in the hepatocytes; however, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the present study and our previous study, 13 peroxisomal proliferation and mitochondrial changes were clearer in females than in males. The changes in both the females and males were slight.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In the present study and our previous study, 13 peroxisomal proliferation and mitochondrial changes were clearer in females than in males. The changes in both the females and males were slight.…”
Section: Discussionsupporting
confidence: 77%
“…These results suggested that the peroxisome proliferation was subtle. In our previous study, 13 we could not reach a conclusion as to whether or not DEHP induced peroxisome proliferation. We added the biopsy before treatment and a vehicle control and increased the number of animals in the present study.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is well known that the administration of some chemicals and a variety of nutritional manipulations induce the appearance of giant mitochondria in experimental animals (Ludatscher and Silbermann 1976; Rohr and Riede 1973; Satake et al 2008; Tandler and Hoppel 1986; Suzuki 1969; Wakabayashi, Asano, and Kawamoto 1979). In humans, giant mitochondria have been reported in a variety of diseases such as steatohepatitis and mitochondrial neurogastrointestinal encephalopathy (Caldwell et al 1999; Perez-Atayde et al 1998).…”
Section: Discussionmentioning
confidence: 99%